Case studies on the transition from traditional classrooms to innovative learning environments: Emerging strategies for success. (July 2020) - French, Raechel; Imms, Wesley; Mahat, Marian
This article explores the characteristics of a successful transition of a school from traditional classrooms to an innovative learning environment. Many schools today are converting traditional classrooms into spaces which are flexible, supporting a wide array of teaching and learning possibilities (i.e. an 'innovative learning environment'). These schools envision a future in which teaching, culture and space align to result in engaged students achieving deep learning. Many of these schools, however, fail to align teaching practices, organisational structures and leadership with their design's intended vision. This results in a misalignment between the pedagogical goals of the building and its subsequent use. Through case studies of four schools in Australia and New Zealand, this study identifies the commonalities between the schools' independent transitions resulting in four shared characteristics of a successful transition from traditional to innovative learning environments – Culture, Nudges, Structure and Expectations. Within each characteristic, specific strategies are provided to enable alignment between the design and use of a school building.